2011
DOI: 10.1186/1742-4690-8-11
|View full text |Cite
|
Sign up to set email alerts
|

Highly conserved serine residue 40 in HIV-1 p6 regulates capsid processing and virus core assembly

Abstract: BackgroundThe HIV-1 p6 Gag protein regulates the final abscission step of nascent virions from the cell membrane by the action of two late assembly (L-) domains. Although p6 is located within one of the most polymorphic regions of the HIV-1 gag gene, the 52 amino acid peptide binds at least to two cellular budding factors (Tsg101 and ALIX), is a substrate for phosphorylation, ubiquitination, and sumoylation, and mediates the incorporation of the HIV-1 accessory protein Vpr into viral particles. As expected, kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
36
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 56 publications
(68 reference statements)
12
36
0
Order By: Relevance
“…Votteler et al (26) reported a processing and infectivity phenotype for an S40F variant of p6. This nonconservative mutation was chosen to avoid potentially confounding changes in the overlapping pol region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Votteler et al (26) reported a processing and infectivity phenotype for an S40F variant of p6. This nonconservative mutation was chosen to avoid potentially confounding changes in the overlapping pol region.…”
Section: Discussionmentioning
confidence: 99%
“…1A and B (see Figure S1 and Tables S1 and S2 in the supplemental material), we selected residues S14, T23, S25, and S51 for mutagenesis. Residue S40 was omitted because a detailed analysis of an HIV-1 p6 mutant, S40F, had recently been performed (26). Residue T8 was not included because it is part of the essential PTAP motif (11), and residue S43 was not included because an S43A mutation had no apparent effect on HIV-1 release (16).…”
Section: Prediction Of Potentially Phosphorylated Amino Acids In Hiv-mentioning
confidence: 99%
See 1 more Smart Citation
“…The overrepresentation of the 483L/484Y motif in the intersubtype recombinants suggests that it is advantageous and may partially contribute to the enhanced replication capacity of these viruses. Residues 483 and 484 are essential residues in a late domain for binding the Alix host protein (65), which acts in concert with the primary budding factor Tsg101 to mediate viral budding (66). Mutants with disrupted Alix binding have significantly reduced particle production and infectivity, demonstrating an important role for Alix in HIV-1 replication (66).…”
Section: Discussionmentioning
confidence: 99%
“…Gag may interrupt the proteolytic cleavage between capsid Gag and SP1 Gag (552). (iii) Neutralizing responsiveness to Nef and glycosylated Gag is determined by GP120 V1/V2 regions (344), whereas it remains unclear whether GP120 physically interacts with Nef or glycosylated Gag.…”
Section: Absence Of Other Hiv Protein Interactionsmentioning
confidence: 99%